ANALYSIS CRIMINOLOGY TO DYNAMICS CONFLICT INTRA-FAMILY AS A CRIMINOGENIC FACTOR IN THE CRIME OF PARRICIDE - Alexandro Aldikan Matio Panjaitan; Bambang Waluyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The family is essentially a primary social institution that serves as a means of fostering, protecting, and shaping individual character. However, under certain conditions, the family can transform into a criminogenic environment that triggers deviant behavior. This research aims For analyze dynamics intra-family conflict Which background action criminal parricide in case Abdullah Syauqi Jamaludin and examines the conflict as a criminogenic factor from a criminological and criminal law perspective. This study uses an empirical-normative legal research method. ( socio-legal research ) with approach legislation, case study approach, and sociological criminology approach. Data were obtained through literature review, case document searches, interviews with police officers, and analysis of relevant laws and regulations. The results of the study indicate that the crime of parricide Which done by defendant Noborn from One factor single, rather, it is an accumulation of economic pressure, relational conflict, family stigma, and verbal violence that occurs repeatedly and continuously. Based on the General Strain Theory analysis put forward by Robert Agnew, these various forms of pressure create a condition of strain that ultimately leads to the occurrence of explosion fatal aggression. From a legal perspective, the Public Prosecutor's application of cumulative charges reflects a comprehensive law enforcement effort across all dimensions of the defendant's criminal acts. This study concludes that the conflict Unresolved intra-family issues can develop into dangerous criminogenic factors and emphasize the importance of a criminalization approach that is not only oriented towards punishment, but also takes into account the social and psychological background of the perpetrator as mandated in the New Criminal Code.